THE INFLUENCE OF INTENTION UTILIZATION AND USE OF ACCOUNTING SOFTWARE ON INDIVIDUAL PERFORMANCE: UNIFIED THEORY APPROACH OF ACCEPTANCE AND USE OF TECHNOLOGY (UTAUT) MODEL - Madani Hatta; Fenny Marietza; Rewa Yoke Desthomson (Jurnal Akuntansi, 2016)
This study aims to determine the influence of utilization intention and use accounting software for individual performance by using a model unifiedtheory of acceptance and use of technology (UTAUT) consisted of performance expectation, effort expectation, social influence, facilitating conditions, the intention of the use of accounting software, the useof accounting software, and the individual performance. The sample in this study were 61 employees of the banking company in the city of Bengkulu who use accounting software in their working activity. The results showed that the performance expectation has significant positive influence to intention utilization accounting software, effort expectation has  significant positive influence to the intention utilization accounting software, social influence has significant positive influence to the use of accounting software intention, facilitating condition has significant positive influence to the use of accounting software, accounting software utilization intention has significant positive influence to the use of accounting software and the use of accounting software has positive influence to the performance of the individual.Key words : Performance Expectation, Effort Expectation, Social Influence, The Facilitating Conditions, Intention Utilization, Use of Accounting Software, UTAUT.